Propiedades psicométricas de la Escala de Autoritarismo de Derechas en población colombiana - García-Sánchez, Efraín (2022)
This article presents the adaptation of a reduced version of the Right-wing Authoritarianism Scale (RWA) in Colombia. In Study 1 (n=417) it was performed an exploratory factor analysis to identify the underlying dimensions of the scale; in Study 2 (n=396), it was performed a confirmatory factor analysis and tested the divergent/convergent validity of the scale. The results suggest that the RWA has three dimensions: authoritarian- aggression, authoritarian-submission, and conventionalism. Additionally, RWA was positively associated with: social dominance, dehumanization of the adversary, armed conflict support, patriotism, sexism, homophobia, and the prohibition of progressive social policies (e.g., abortion, homosexual marriage, euthanasia). Empirical evidence is provided in favor of appropriate psychometric properties for the RWA scale in the Colombian context.